Gastric manometric abnormalities in patients with dyspeptic symptoms after fundoplication. - Stanghellini, V (1983)
We describe six patients in whom severe dyspeptic symptoms developed after fundoplication. The symptoms began immediately after operation (three patients) or shortly thereafter (three and eight months). There were no other known predisposing factors to gastroparesis. Seven, age-matched, healthy volunteers served as controls. Pressure activity from antrum (two sites), duodenum (two sites), and jejunum (one site) was recorded by a low compliance perfusion system connected to external strain gauge transducers. Activity was recorded for three hours during fasting and for two hours after the ingestion of a solid and a liquid meal. To determine whether an inadvertent vagotomy had been performed, basal acid output and the response to insulin (Hollander's test) were measured on a separate day. Manometric studies revealed postprandial hypomotility in these patients, whereas fasting antral and intestinal activities were normal. Acid output increased in all patients during insulin induced hypoglycaemia. In three patients, an antrectomy was subsequently performed, and they were relieved of their symptoms. We conclude that, after fundoplication, symptoms associated with postprandial antral hypomotility may develop in some patients. The pathophysiologic mechanism is unknown, but a positive acid response to insulin induced hypoglycaemia does not support the occurrence of incidental vagotomy. We do not know the prevalence of this motor abnormality among asymptomatic patients with prior fundoplication. A favourable symptomatic response to antrectomy in several of our patients, however, suggests that the symptoms were related to antral motor dysfunction.